THE INFLUENCE OF RUPIAH EXCHANGE RATE, FIRM SIZE, LEVERAGE AND LIQUIDITY ON HEDGING DECISIONS - Rachmat, Adrianna Syariefur; Kustina, Lisa (Journal of Research in Business, Economics, and Education, 2019)
Companies facing the risk of fluctuations in foreign exchange rates can hedge with derivative instruments such as forward, future, swap and option contracts. The purpose of this study is to determine the effect of exchange rates, firm size, leverage and liquidity on hedging decision making using derivative instruments at state-owned banks listed on the Indonesia Stock Exchange for the period of 2016-2018. The method of determining the sample using purpose sampling technique and obtained 12 samples that meet the criteria and 144 firm-quarter observation. The analysis technique used is regression panel logistics. Based on research results obtained, that if the size of the company increases, the potential for hedging decisions through derivative instruments also increases. As for the level of leverage increases, the potential for hedging decisions through derivative instruments decreases. And if the level of liquidity increases, the potential for hedging decisions through derivative instruments decreases.